2016
DOI: 10.12693/aphyspola.130.795
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Performance of Purple Carrot Sensitized Solar Cells by Acidic Treatment of FTO Glass Substrate and TiO2Film

Abstract: In this paper, dye sensitized solar cells were prepared using titanium dioxide (TiO2) and natural dye extracted from purple carrot. The performance of dye sensitized solar cells was significantly improved through the pre-and post-treatments of the fluorinated tin oxide (FTO) glass substrate and the TiO2 film using hydrochloric (HCl), phosphoric (H3PO4), and nitric (HNO3) acids. The results showed that the pre-treatment of the FTO with H3PO4 and the post-treatment of TiO2 with HNO3 resulted in improved efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Batniji et al worked on Trigonella used as sensitizers in DSSCs and achieved 0.215% efficiency . Radwan et al found 0.81% efficiency for DSSCs based on natural purple carrot . Taya et al employed natural dyes of Safflower, Medicago sativa , and Ros marinus and reached 0.115% efficiency…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Batniji et al worked on Trigonella used as sensitizers in DSSCs and achieved 0.215% efficiency . Radwan et al found 0.81% efficiency for DSSCs based on natural purple carrot . Taya et al employed natural dyes of Safflower, Medicago sativa , and Ros marinus and reached 0.115% efficiency…”
Section: Introductionmentioning
confidence: 99%
“…21 Radwan et al found 0.81% efficiency for DSSCs based on natural purple carrot. 22 Taya et al employed natural dyes of Safflower, Medicago sativa, and Ros marinus and reached 0.115% efficiency. 23 In this study, three different DSSCs with varying natural sensitizers yellow jasmine berry, madder berry, and St. Lucie cherry fruits were fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…The FTO glasses rinsed with DI water were then heat treated [61] on a hot plate for 10 min at 125 • C for drying, then at 450 • C for 30 min. The TiO 2 paste was ground in a mortar for at least 30 min by adding it into 7 gr TiO 2 nano-powder (Aeroxide TiO 2 P25, 20-25 nm particle size) in HNO 3 [62][63][64] aqueous solution 1.5M in 1 mL increments while it was ground for the mechanical separation of the aggregated TiO 2 particles until a uniform paste was achieved. The uniform paste was put in an ultrasonic bath for 5 min to breakdown any agglomerates of TiO 2 nanoparticles that were not broken up.…”
Section: Materials and Fabrication Methodsmentioning
confidence: 99%
“…Obviously, synthetic dyes have higher sensitization activity and stability than natural dyes [10,14]. The natural dyes used as sensitizers in DSSCs provide very low efficiencies because of the absence of specific functional attachment groups and low absorption in the visible region of the solar spectrum [54][55][56][57][58]. Zhang et al [59] synthesized three synthetic dyes and studied them by using a TiO 2 photoanode and observed efficiencies as high as 7.6 %, which are higher than those of natural dyes.…”
Section: Photoelectrochemical Characteristics Of Zno Dsscsmentioning
confidence: 99%